Management of Rare Secondary Full-Thickness Macular Hole in Proliferative Diabetic Retinopathy: Inverted ILM Flap Technique with Extended Surgical Follow-up - I Gusti Ngurah Dhyana Yoga; Ari Andayani; Ni Made Ari Suryathi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Secondary full-thickness macular hole (FTMH) in proliferative diabetic retinopathy (PDR) is rare, occurring in only 1-4% of PDR cases. Combined with tractional retinal detachment (TRD), this complication presents significant surgical challenges. The inverted internal limiting membrane (ILM) flap technique remains under-utilized in this specific setting. Case presentation: A 61-year-old Indonesian male with type 2 diabetes (>15 years), chronic kidney disease, and cardiovascular disease presented with sudden vision loss (best-corrected visual acuity 1/300). Examination revealed superior TRD (2-11 o'clock) and large FTMH (CMT 249 micrometers). After intravitreal bevacizumab (August 9th, 2024), he underwent 360-degree pars plana vitrectomy with inverted ILM flap and silicone oil tamponade (August 14th, 2024). Inferior redetachment at 2 months necessitated re-vitrectomy with endolaser and silicone oil evacuation (October 23rd, 2024). At final follow-up (12 weeks post-second surgery), the patient achieved complete retinal reattachment with normalized macular anatomy, visual acuity 1/60, and intraocular pressure 10 mmHg. Conclusion: Despite severe baseline disease and comorbidities, stepwise surgical strategy incorporating preoperative anti-VEGF therapy, comprehensive traction release, inverted ILM flap reconstruction, and staged procedures yielded meaningful anatomical recovery. This case supports inverted ILM flap utility in PDR-related secondary FTMH.